2013
DOI: 10.3109/s10165-012-0644-7
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic thrombocytopenic purpura with an autoantibody to ADAMTS13 complicating Sjögren’s syndrome: two cases and a literature review

Abstract: An association between thrombotic thrombocytopenic purpura (TTP) and Sjögren's syndrome (SS) is rare. This is the first report of two patients with TTP who had inhibitory autoantibodies to ADAMTS13 (a disintegrin-like and metalloprotease with thrombospondin type 1 repeats) complicating primary SS. A rapid diagnosis of TTP, which is a potentially lethal condition, made it possible to treat the two cases successfully. Only eight similar cases with TTP complicating SS have been reported in the literature. The pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Given that there were no other predisposing factors for TTP in this patient, the cause of TTP was considered tobe closely related to her pregnancy and pSS. To the best of our knowledge, only three cases of aTTP combined with pSS have been reported in the past 20 years, and none were associated with pregnancy [ 24 26 ]. Our case emphasises the importance of screening for collagen disease during pregnancy, including pSS, even if the patient is asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Given that there were no other predisposing factors for TTP in this patient, the cause of TTP was considered tobe closely related to her pregnancy and pSS. To the best of our knowledge, only three cases of aTTP combined with pSS have been reported in the past 20 years, and none were associated with pregnancy [ 24 26 ]. Our case emphasises the importance of screening for collagen disease during pregnancy, including pSS, even if the patient is asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with an autoimmune disorder are at risk for additional autoimmune diseases, resulting in various combinations including immune-hemolytic anemia, 3 systemic lupus erythematosus, 4 Sj€ ogren syndrome, 5 systemic sclerosis, 6 and others. However, we found only six reported cases of concomitant TTP and GD (Table 1), [7][8][9][10][11][12] although several mechanisms have been proposed in which GD may be causally related to TTP.…”
Section: Discussionmentioning
confidence: 99%
“…Steroids were discontinued at 6 months, and after one year the patient is off medication, without signs of TTP or SS extraglandular activity. TTP can co-occur with autoimmune diseases (AID) (1). A review identified 18 cases of concomitant SS and TTP (16 in primary SS) (2).…”
mentioning
confidence: 99%